2017
DOI: 10.3389/fped.2017.00007
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Fecal Calprotectin Measurement on Decision-making in Children with Inflammatory Bowel Disease

Abstract: BackgroundThe use of fecal calprotectin (FCal) as a marker of intestinal inflammation, in the management of inflammatory bowel disease (IBD) is increasing. The aim of this study was to examine the impact of FCal measurements on decision-making and clinical care of children with IBD.Materials and methodsIn a retrospective cohort study, FCal, clinical activity indices, and blood markers were measured in children with established diagnoses of IBD. Pearson correlation coefficient analysis was performed to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
3
9
0
2
Order By: Relevance
“…However, with knowledge of the FC level, physicians would have performed endoscopy in 16 of the 36 patients. Another study showed that 12% of pediatric patients with CD or UC underwent colonoscopy after FC measurement [27]. Our present study is in line with the above, with 12% (28/242) of our adult IBD cohort undergoing a colonoscopy.…”
Section: Discussionsupporting
confidence: 91%
“…However, with knowledge of the FC level, physicians would have performed endoscopy in 16 of the 36 patients. Another study showed that 12% of pediatric patients with CD or UC underwent colonoscopy after FC measurement [27]. Our present study is in line with the above, with 12% (28/242) of our adult IBD cohort undergoing a colonoscopy.…”
Section: Discussionsupporting
confidence: 91%
“…It is clear that GT is an inflammatory condition, given that the level of calprotectin is increased in the saliva of these patients. In other studies, for example, those investigating IBD, the levels of calprotectin were higher when the disease was present, and these levels correlated with the grade of disease (El‐Matary et al, ).…”
Section: Discussionmentioning
confidence: 86%
“…The level of fecal calprotectin is used in gastroenterology to assess the grade of intestinal inflammation (Tibble et al, ). A positive correlation between increased concentrations of fecal calprotectin and more severe clinical disease has been reported for inflammatory bowel diseases (IBD) (El‐Matary, Abej, Deora, Singh, & Bernstein, ). In infectious and inflammatory conditions, the level of calprotectin is usually increased (Berntzen, Fagerhol, Ostensen, Mowinckel, & Hoyeraal, ; Sander, Fagerhol, Bakken, & Dale, ).…”
Section: Introductionmentioning
confidence: 97%
“…ACCA "anti-chitobioside carbohydrate antibodies", ALCA "anti-laminaribioside carbohydrate antibodies", AMCA "anti-mannobioside carbohydrate antibodies", Anti-C "anti-chitin carbohydrate antibodies", Anti-CBir1 Antikörper gegen das bakterielle Flagellin CBir1, Anti-GP2 Antikörper gegen Glykoprotein 2, Anti-I2 Antikörper gegen die "pseudomonas-associated sequence", Anti-L "anti-laminarin carbohydrate antibodies", Anti-OmpC Antikörper gegen "outer membrane porin C of Escherichia coli", ASCA Antikörper gegen Saccharomyces cerevisiae, CD "Crohn's disease" (M. Crohn), GAB Antikörper gegen "intestinal goblet cells" (Becherzellen des Darms), ND "no data available" (keine Daten erhältlich), PAB "pancreatic antibodies", PPV "positive predictive value" (positiver Vorhersagewert), UC "ulcerative colitis" (Colitis ulcerosa) ASCA "anti-Saccharomyces cerevisiae antibodies", Anti-GP2 Antikörper gegen Glykoprotein 2, CU Colitis ulcerosa, GAB Antikörper gegen Becherzellen des Darms, MC M. Crohn, PAB "pancreatic antibodies", pANCA "perinuclear anti-neutrophil cytoplasmic antibodies", PPV positiver Vorhersagewert, rPAB "recombinant pancreatic antigen" fitäten um 83 % [10]. Ergänzend stellte eine pädiatrische Studie mit fast 80 Kindern fest, dass Therapieintensivierungen -lediglich aufgrund steigender FC-Werte -generell eine klinische Besserung bewirkten und die Messung nur dieses einen Parameters daher wesentlich war [11]. Wie sich ein anderer fäkaler Biomarker, Lactoferrin, im Vergleich zu FC beurteilen lässt, ist einem systematischen Review von 19 Studien mit fast 2500 Patienten mit aktiver CED zu entnehmen: Der Vergleich von CRP, FC, Stuhl-Lactoferrin und dem endoskopischen Befund als "Goldstandard" ergab für das CRP eine Sensitivität von 0,49 bezüglich der endoskopisch aktiven Erkrankung (Spezifität 0,92).…”
Section: Laboratory Diagnostics In Chronic Inflammatory Bowel Diseaseunclassified